Innovation in Product Design From CAD to Virtual Prototyping - Bordegoni, Monica; Rizzi, Caterina (Springer London, 2011)
Innovation in Product Design gives an overview of the research fields and achievements in the development of methods and tools for product design and innovation.  It presents contributions from experts in many different fields covering a variety of research topics related to product development and innovation. Product lifecycle management, knowledge management, product customization, topological optimization, product virtualization, systematic innovation, virtual humans, design and engineering, and rapid prototyping are the key research areas described in the book. It also details successful case studies developed with industrial companies. Innovation in Product Design is written for academic researchers, graduate students and professionals in product development disciplines who are interested in understanding how novel methodologies and technologies can make the product development process more efficient.